THE FULL MEMBERSHIP OF THE REPUBLIC OF LITHUANIA IN THE EUROPEAN UNION AS A CONSTITUTIONAL VALUE - Egidijus Jarašiūnas (Public Policy and Administration, 2018)
The article analyses the legal significance of the application of the concept of the full membership of the Republic of Lithuania in the European Union as a constitutional value in the jurisprudence of the Constitutional Court of the Republic of Lithuania. This idea is only acceptable in the context of the concept of a Constitution as an act establishing and protecting a specific system of values. It also reflects the openness of Lithuania’s constitutional law to international law and European integration. The full membership of the Republic of Lithuania in the European Union is treated by the Lithuanian Constitutional Court as an element of the principle of the geopolitical orientation of the Lithuanian state, which is closely interrelated with the fundamental constitutional values (state independence, democracy and republic, etc.). Therefore, it is in the so-called “constitutional core”, between the fundamental constitutional principles and values on which the constitutional system is based. This is one of the peculiarities of our constitutional system. Recognition of the status of a constitutional value presupposes the problems for Constitutional Court in appreciating the content and significance of this value and its relationship with other constitutional values. The balancing of the full membership of the Republic of Lithuania in the European Union as a constitutional value with other constitutional values is at the centre of constitutional interpretation. Moreover, it also relates to the problems of the axiological interpretation of the Constitution. The full membership of the Republic of Lithuania as a value is one of the elements of the constitutional principle of geopolitical orientation, which arises in constitutional jurisprudence as an element of constitutional identity. One of the aspects of the use of the concept of constitutional identity is the opposition of constitutional and European identity (constitutional identity is understood in this case as an instrument of self-defence against excessive integration). The Lithuanian constitutional concept, which declares that the full membership of the Republic of Lithuania in the European Union is a constitutional value and an element of constitutional identity, means that in the analysis of the legal problems of the interaction of the national and European Union legal systems, we must not simply view relations as “our own” and “foreign”, but the interaction between “our own” and “our own from a wider perspective”. This concept means that the constitutional identity cannot only be treated as an instrument for protecting the national system, but also as a measure for the well-founded establishment of balance between the national and EU legal systems.